P2Y12 inhibitors monotherapy in patients undergoing complex vs. non-complex percutaneous coronary intervention: a meta-analysis of randomized trials. (3rd October 2022) - Oliva, A; Castiello, D; Franzone, A; Condorelli, G; Colombo, A; Esposito, G; Stefanini, G; Piccolo, R
Abstract: Background: Monotherapy with P2Y12 inhibitors (P2Y12i) is emerging as alternative strategy to dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI). However, early withdrawal of aspirin as part of P2Y12i monotherapy regimens may pose concerns in high-risk patients, such as those undergoing complex PCI. Purpose: To evaluate the efficacy and safety of P2Y12i monotherapy after a short course of DAPT (1- to 3-month) compared with standard DAPT (≥12-month) according to PCI complexity. Methods: We performed a meta-analysis of randomized trials using random effects models to combine hazard ratios (HRs) with 95% confidence intervals (CIs). No restrictions were applied to the type of P2Y12 receptor inhibitor (clopidogrel, prasugrel, or ticagrelor) or to the definition of complex PCI. Within-trial interactions were pooled to estimate heterogeneity between complex and noncomplex PCI strata. The study protocol was registered in the PROSPERO (CRD42021291027). Results: We screened 7, 502 unique citations, of which 2, 948 were screened at title and abstract level and 576 were judged potentially eligible for full-text assessment. We included in the analysis five trials (1–5) enrolling 31, 627 patients, of whom 8, 328 (26.3%) underwent complex PCI; characteristics of trials and patient populations are summarized in Table 1. Risk estimates for efficacy and safety outcomes associated with P2Y12i monotherapy and standard DAPT across studies included in the analysis, stratified by complex and noncomplex PCI, are reported in Figure 1. P2Y12i monotherapy compared with standard DAPT was associated with a similar risk of all-cause death, stent thrombosis, and stroke, with no evidence for interaction between complex and noncomplex PCI. We found heterogeneity in the treatment effect of P2Y12i monotherapy vs. standard DAPT with respect to myocardial infarction (P-interaction=0.027). Compared with standard DAPT, P2Y12i monotherapy decreased the risk of myocardial infarction in complex PCI (HR 0.77, 95% CI 0.60–0.99, P=0.042), but not in noncomplex PCI patients (HR 1.09, 95% CI 0.90–1.30, P=0.382). The risk of major bleeding was significantly reduced by P2Y12i monotherapy with a consistent treatment effect (P-interaction=0.699) in both complex and noncomplex PCI strata. Conclusions: Patients undergoing complex PCI may derive more benefit and less harm from P2Y12i monotherapy after early aspirin withdrawal compared with standard DAPT, resulting in decreased risks of myocardial infarction and bleeding. Funding Acknowledgement: Type of funding sources: None.